Sequence and Expression Analysis of virB9 of the Type IV Secretion System of Ehrlichia canis Strains in Ticks, Dogs, and Cultured Cells - Felek, Suleyman (American Society for Microbiology, 2003)
Ehrlichia canis virB9 was cloned and expressed. The sequences of virB9 from six geographic locations were identical. virB9 was transcribed by E. canis in dogs, ticks, and cell culture. Infected dogs had antibodies to recombinant VirB9, indicating that VirB9 was produced by E. canis in dogs and was antigenic.